PROSES PELAKSANAAN AKAD QARDH WAL IJARAH PADA PRODUK TALANGAN HAJI PADA BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU PADANG PANJANG - Awaluddin, Awaluddin (JURIS (Jurnal Ilmiah Syariah), 2016)
The agreement of qardh wal ijarah for the product of pilgrimage bailout has been implemented by some sharia banks In Indonesia following fatawa of DSN No. 29/DSN-MUI /IV/2002 about product of pilgrimage bailout. In one side, this implementation made much easier for those to realize their dreams to go for pilgrimage. On the other side, such implementation raised a very challenging question whether  the implemtatation has fulfilled the rules expected by the fatawa. Based on a study conducted, it revealed that the process of proposing product of pilgrimage bailout by the customers of BSM of Kota Padang Panjang supporing branch office was done as it was required by the mechanism by considering 5C factors as standard procedure for realizing the finance. In realizing pilgrimage bailout, this institution referred to the fatawa of  MUI about pilgrimage bailout in which the customer should have settled the bailout before the depart to pilgrimage. This also implies that the bank has the rights to cancel the customers’ departure in the case of inability to settle the bailout. Dealing with this implementatiom, bank is benefited  from the ujroh based on the agreement between the bank and the customer. Customers, on the other hand, are required to pay expenses dealing administration and insurance as the consequences of the agreement. Furthermore, the customers are benefitted from  gaining portion ahead and are allowed to pay in installments for the pilgrimage.